Response of river delta hydrological connectivity to changes in river discharge and atmospheric frontal passage - Feizabadi, Sajjad; Li, Chunyan; Hiatt, Matthew (Frontiers in Marine Science, 2024)
Atmospheric frontal passage is a common meteorological event that can significantly affect hydrodynamics in coastal environments, including the hydrological connectivity between channels and floodplains that regulates material transport in river deltas. This study is focused on the influence of atmospheric cold fronts on the hydrological connectivity between channels and floodplains within the Wax Lake Delta using the Delft3D FM model. The results demonstrate a substantial effect of passing cold fronts on the exchange of water and transport fraction between the primary channels and floodplains. This impact is intricately connected to the morphodynamical characteristics of the floodplains, the intensity of cold fronts, river discharge, Coriolis force, and tidal currents. The passing cold fronts can enhance or reverse the direction of water exchange between channels and floodplains. For floodplains, the passage of cold fronts can lead to an increase in the rate of water exchange by as much as five times. In the WLD, a substantial fraction of water, 39-58%, is flowing through the floodplains to the bay at the delta front influenced by the prevailing discharge, although there is a significant spatial heterogeneity. Passing cold fronts can alter the transport distribution, depending on the phase of the front. An increase in river discharge tends to bolster floodplain connectivity and lessen the effects of cold fronts. Conversely, decreased river discharge results in reduced connectivity and exacerbates the fluctuations induced by cold fronts. Moreover, the findings indicate that from the apex to downstream, the contribution of channels decreases as they become shallower, while the role of the floodplains increases, leading to a less distinct demarcation between channels and floodplains. It has also been noted that an increase in river discharge correlates with an increased contribution from floodplains to transfer water to the bay.